Current dietary supplement use of Australian military veterans of Middle East operations. Issue 17 (15th August 2017) - van der Pols, Jolieke C; Kanesarajah, Jeeva; Bell, Alison; Lui, Chi-Wai
Abstract: Objective: To assess patterns and levels of dietary supplement use among Australian Defence Forces, previously deployed to the Middle East Area of Operations. Design: A cross-sectional study. Participants of a large survey self-completed questions about dietary supplement use, health status, personal and job-related characteristics, and lifestyle factors. Frequency of current use of supplements was assessed in three categories (bodybuilding, energy and weight loss). Setting: Middle East Area of Operations post-deployment health survey. Subjects: Current and ex-serving Australian Defence Force personnel ( n 14 032) who deployed to the Middle East between 2001 and 2009. Results: Bodybuilding supplements were used by 17·5 % of participants, energy supplements by 24·5 % and weight-loss supplements by 7·6 %. Overall, 32·3 % of participants used any of these supplements. Bodybuilding and energy supplements were more often used by men, younger persons and those in the Army, while weight-loss supplements were more commonly used by women and Navy personnel. Supplements in all three categories were more commonly used by persons in lower ranks, active service and combat roles. Users of bodybuilding supplements had healthier lifestyles and better health status, while users of energy and weight-loss supplements had less healthy lifestyles and poorer mental and physical health status. Overall, 11·7 % of participants used supplements containing caffeine and 3·6 % used a creatine-containing product. Conclusions: Use of dietary supplements among Australian Defence Force personnel is common, and patterned by lifestyle factors and health status.